The Effect Of Puzzle Game For Early Literacy Achievement of Underachiever Students - Susi Susi Susiani; Ketut Herya Dhrama Utami (Bisma The Journal of Counseling, 2020)
Early literacy skills are the capacity to name letters and write them down, spell simple words, recognize letters and signs around them, identify books from titles, and perform book-related activities. Early literacy consists of nine components, namely language, rules/provisions/habits, knowledge of letters, awareness of language elements, the suitability of phonemes, pretend reading, pretend writing, notation, and cognitive skills. However, mentally retarded children only emphasize the recognition of vowels as the basis of initial literacy. This study aims at determine the effect of game media puzzle to improve initial literacy skills through vowel recognition for mild second-grade mentally retarded students. This study uses a case study. The sampling technique that will be used by researchers is to use quantitative and qualitative analysis techniques. Quantitative analysis with simple statistics is used in the survey results to see students' understanding of learning vowels. Qualitative analysis techniques are used in the results of interview data, focus group discussions, observation and documentation. The number of samples used was 3 students from 6 class II students. The research instrument was in the form of observations and interviews. The results of the observation indicate that the average value before being given treatment is 6.0 and the value after being given media treatment is 8.7. Thus it can be predicted the application of game media puzzle effective to improve initial literacy skills through vowel recognition for mild second-grade mentally retarded students.